(untitled) (Prostor, 2025)
In Architecture Follows Fish, André Tavares explores how fishing practices and marine ecologies shaped architecture across the North Atlantic. Introducing the idea of “fishing architecture,” the author frames buildings as outcomes of human–nature entanglements. The book challenges anthropocentric views, offering a critical, ecological lens on architecture while seeking more integrated, relational understandings of the world we build and inhabit.